The Influence of Marketing Strategy and Brand Image on Customer Loyalty with Customer Satisfaction as a Mediating Variable among Customers of BSI Bank, Kedaton Branch - sulfan sulfan basten; Any Eliza; Anas Malik (Universitas Islam Negeri (UIN) Walisongo Semarang, 2025)
Purpose - This study aims to analyze the influence of marketing strategies and brand image on customer loyalty, with customer satisfaction as a mediating variable at BSI Bank Kedaton Branch. Method - The research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling. The respondents are customers of conventional services and active users of the BSI Mobile application. Result - The results of the study showed that marketing strategies and brand image affect BSI bank customer loyalty. Marketing strategies and brand image are able to influence BSI bank customer satisfaction, and customer satisfaction as a mediating variable is able to mediate marketing strategies and brand image on BSI bank loyalty. Implication - This study provides practical insights for Islamic banking institutions to increase customer loyalty by improving their marketing strategies and strengthening brand image through customer satisfaction. Originality - The novelty of this research lies in its integrated analysis of customer satisfaction as a mediating variable between marketing strategies and brand image toward customer loyalty in the context of a newly merged Islamic bank, BSI. Keywords: Marketing strategy, brand image, customer loyalty, customer satisfaction.